Variation in health system performance for managing diabetes among states in India: a cross-sectional study of individuals aged 15 to 49 years - Prenißl, Jonas; Jaacks, Lindsay M.; Mohan, Viswanathan; Manne-Goehler, Jennifer; Davies, Justine I.; Awasthi, Ashish; Bischops, Anne Christine; Bärnighausen, Till; Vollmer, Sebastian; Geldsetzer, Pascal (BMC medicine, 2019)
Understanding where adults with diabetes in India are lost in the diabetes care cascade is essential for the design of targeted health interventions and to monitor progress in health system performance for managing diabetes over time. This study aimed to determine (i) the proportion of adults with diabetes in India who have reached each step of the care cascade and (ii) the variation of these cascade indicators among states and socio-demographic groups.
Gesehen am 24.07.2019